The Pneumocystis Intestinalis with Porto-Mesenteric Venous Gas - Serdar Özdemir; İbrahim Altunok (Hitit Medical Journal, 2020)
A 71-year-old female patient was admitted to emergency department with a general condition disorder and fever. She had a history of stroke, hypertension and diabetes, and had a history of operation for colon carcinoma 2.5 years ago. On examination, his consciousness was stupor. Intra-venous contrast-enhanced computed abdominal tomography showed diffuse distension consistent with ileus in small bowel segments. Intramural gas images were seen in the distal ileal segments. Gas images compatible with portal system were present in the liver. Emergency laparotomy was performed. It was observed that the 40 cm small bowel loops adhered to the posterior abdominal wall of the pelvis and necrosis of this segment was observed during the operation.